Trabecular bone structure scales allometrically in the foot of four human groups. Issue 135 (October 2019) - Saers, Jaap P.P.; Ryan, Timothy M.; Stock, Jay T.
Abstract: The human foot is highly derived relative to that of other hominoids and therefore a topic of intense research in paleoanthropology. While trabecular bone is thought to be highly plastic in response to habitual behavior, knowledge of how trabecular structure scale with body size is essential for making functional inferences from trabecular bone morphology. Trabecular bone properties scale with negative allometry in interspecific studies that includes a wide range of body size; however, intraspecific scaling patterns often differ from interspecific trends. In this paper we examine patterns of trabecular bone scaling in the calcaneus, talus, and first metatarsal of four human populations with different subsistence strategies and associated levels of terrestrial mobility. We report Bayesian linear regressions between the natural logarithms of femoral head diameter and five standard trabecular variables calculated in five spherical volumes of interest. We additionally report regressions on population-specific z-scores of femoral head diameter and trabecular variables as a way of placing the four populations on a common scale. Results show that with increasing body size there is no change in bone volume fraction (BV/TV) and trabecular thickness (Tb.Th), a slight increase in trabecular spacing (Tb.Sp), and a sharp decrease in connectivity density (Conn.D). Degree of anisotropy was found to scale with positive allometry in the calcaneus, negative allometry in the talar trochlea, and shows no relationship with femoral head diameter in the talar and first metatarsal heads. These results show that scaling of the degree of anisotropy can vary substantially within and between bones. Degree of anisotropy is often used as a proxy for directionality in joint loading when interpreting variation in trabecular structures of fossils and extant primates. Body size should therefore be an important consideration when trabecular bone structure is used to interpret function from fossil morphology.